2009
DOI: 10.1139/p09-108
|View full text |Cite
|
Sign up to set email alerts
|

Student diversity and the persistence of gender effects on conceptual physics learning

Abstract: At Ryerson University every year, hundreds of science and engineering students enroll into required introductory physics courses. The diverse educational histories and demographic characteristics of these students reflect the diversity of Toronto as an urban metropolis and Canada more generally. In this study, we investigate how students’ demographic and educational diversity affects their conceptual learning in introductory university physics. As expected, we found that the completion of a senior high school … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…A pattern of females having lower pre-test scores on conceptual assessments than males has been revealed in physics education research (e.g., Docktor & Heller, 2008;Kost, Pollock, & Finkelstein, 2007;Noack, AN EXAMINATION BY GENDER AND MAJOR 128 Antimirova, & Milner-Bolotin, 2009). For example, Kost, Pollock, and Finkelstein (2007) found that a greater percentage of females were in the low pre-test score group than males when given the Force and Motion Concept Evaluation (FMCE) (Thornton & Sokoloff, 1998).…”
Section: Gender and Cognitive Outcomesmentioning
confidence: 83%
See 4 more Smart Citations
“…A pattern of females having lower pre-test scores on conceptual assessments than males has been revealed in physics education research (e.g., Docktor & Heller, 2008;Kost, Pollock, & Finkelstein, 2007;Noack, AN EXAMINATION BY GENDER AND MAJOR 128 Antimirova, & Milner-Bolotin, 2009). For example, Kost, Pollock, and Finkelstein (2007) found that a greater percentage of females were in the low pre-test score group than males when given the Force and Motion Concept Evaluation (FMCE) (Thornton & Sokoloff, 1998).…”
Section: Gender and Cognitive Outcomesmentioning
confidence: 83%
“…First, they have been used as pre-tests to determine students' prior knowledge. Differences in pre-test scores among students in the same physics class have been found (Kost, Pollack, & Finkelstein, 2007;Noack, Antimirova, & Milner-Bolotin, 2009). Even more, disturbing is that some research has found that discrepancies between those who scored higher and those who scored lower on pre-tests were maintained throughout an entire course (Noack, Antimirova, & Milner-Bolotin, 2009).…”
Section: Assessing Misconceptions With Concept Inventoriesmentioning
confidence: 99%
See 3 more Smart Citations